Hepatocellular carcinoma recurrence after direct-acting antiviral therapy: an individual patient data meta-analysis. Issue 3 (19th March 2021) - Sapena, Victor; Enea, Marco; Torres, Ferran; Celsa, Ciro; Rios, Jose; Rizzo, Giacomo Emanuele Maria; Nahon, Pierre; Mariño, Zoe; Tateishi, Ryosuke; Minami, Tatsuya; Sangiovanni, Angelo; Forns, Xavier; et al.
Abstract : Objective: The benefit of direct-acting antivirals (DAAs) against HCV following successful treatment of hepatocellular carcinoma (HCC) remains controversial. This meta-analysis of individual patient data assessed HCC recurrence risk following DAA administration. Design: We pooled the data of 977 consecutive patients from 21 studies of HCV-related cirrhosis and HCC, who achieved complete radiological response after surgical/locoregional treatments and received DAAs (DAA group). Recurrence or death risk was expressed as HCC recurrence or death per 100 person-years (100PY). Propensity score-matched patients from the ITA.LI.CA. cohort (n=328) served as DAA-unexposed controls (no-DAA group). Risk factors for HCC recurrence were identified using random-effects Poisson. Results: Recurrence rate and death risk per 100PY in DAA-treated patients were 20 (95% CI 13.9 to 29.8, I 2 =74.6%) and 5.7 (2.5 to 15.3, I 2 =54.3), respectively. Predictive factors for recurrence were alpha-fetoprotein logarithm (relative risk (RR)=1.11, 95% CI 1.03 to 1.19; p=0.01, per 1 log of ng/mL), HCC recurrence history pre-DAA initiation (RR=1.11, 95% CI 1.07 to 1.16; p<0.001), performance status (2 vs 0, RR=4.35, 95% CI 1.54 to 11.11; 2 vs 1, RR=3.7, 95% CI 1.3 to 11.11; p=0.01) and tumour burden pre-HCC treatment (multifocal vs solitary nodule, RR=1.75, 95% CI 1.25 to 2.43; p<0.001). No significant difference was observed in RR between the DAA-exposed and DAA-unexposed groups in propensity score-matched patients (RR=0.64, 95% CI 0.37 to 1.1; p=0.1). Conclusion: Effects of DAA exposure on HCC recurrence risk remain inconclusive. Active clinical and radiological follow-up of patients with HCC after HCV eradication with DAA is justified.